Study of recombination in porcine reproductive and respiratory syndrome virus (PRRSV) using a novel in-vitro system - Chand, Ranjni Jagdish (Kansas State University, 2013)
Mechanisms for mutations in RNA viruses include random point mutations, insertions, deletions, recombination and re-assortment. Most viruses have more than one of these mechanisms operating during their life cycle. Impact of sequence divergence is seen in the areas of evolution, epidemiology and ecology of these viruses. Immediate negative consequences of genetic diversity include failure of vaccination, resistance to anti-virals, emergence and re-emergence of novel virus isolates with increased virulence or altered tropism. To identify specific sequence features that influence recombination, a new in-vitro system was developed using an infectious cDNA clone of PRRS virus that expressed fluorescent proteins. The in-vitro experimental system involved the co-transfection of a pair of closely related PRRSV infectious clones: a fully functional non-fluorescent PRRS virus infectious clone that possessed a single mutation in a green fluorescent protein (GFP) and a second infectious clone that contained a defective fluorescent virus. The readout for successful recombination was appearance of a fully functional fluorescent virus. The model system creates the opportunity to study several aspects of recombination, including the requirement for sequence homology between viruses undergoing recombination.
Keywords: Porcine reproductive and respiratory syndrome virus; PRRS; Recombination; RNA virus; In-vitro; Green fluorescent protein; Molecular Biology (0307); Veterinary Medicine (0778); Virology (0720)